VALIDASI METODE ANALISA PENETAPAN KADAR EPIGALOKATEKIN GALAT DENGAN KROMATOGRAFI CAIR KINERJA TINGGI - Sugihartini, Nining; Fudholi, Achmad; Pramono, Suwidjiyo; Sismindari, Sismindari (Pharmaciana, 2014)
High Performance Liquid Chromatography (HPLC) was one of analytical methodscommonly used to determine the concentration of epigallocatechin gallate (EGCG) on green teaextract. The method must be validated in order to fit to its purpose. The aim of this research was toprove that the used method has selectifity, liniearity, precise, accurate and know limit of detection(LOD) and limit of quantification (LOQ) is acceptable. The selectivity of analytical method wasdetermined by calculating the resolution value between two peak. Data from 10 μg/mL and100 μg/mL with 5 replicates would give precition and accuration. Precition was known from CV value and accuration was known from recovery value in each concentration. Liniearity was knownfrom regression linear between concentration and wide area of peak. From regresion linear couldcalculate LOD and LOQ. Research show that method of analyse have selectificity withRs= 2.27>1.5; liniearity with r= 0.99; precision with CV 8.74% at concentration 200 µg/mL and3.74% at concentration 500 µg/mL; accuration with recovery 99.76% at concentration 200 µg/mLand 100.52% at concentration 500 µg/mL and the value of LOD is 33.28 μg/mL and LOQ is110.93 μg/mL.